Vitamin C elicits protection against cylophosphamide-induced nephrotoxicity in rat animal model: Vitamin C Memproteksi Terhadap Nefrotoksisitas Yang Diinduksi Siklofosfamid Pada Hewan Model Tikus - Alifah Dwi Yulianti; Yulia Yusrini Djabir; Prihantono Prihantono (Universitas Tadulako, 2023)
Background: Cyclophosphamide (CPD) causes renal cell toxicity due to its toxic metabolites. Objectives: This study aimed to evaluate the nephroprotective effect of vitamin C at 125 mg/kgBW, 250 mg/kgBW, and 500 mg/kgBW doses based on the biomarker level of urea, creatinine, parameter of urinalysis and renal histopathology. Material and Methods: The experimental animals consisted of 25 rats (Rattus norvegicus) that were divided into 5 treatment groups: healthy control, placebo (water for injection + CPD 250mg/kgBB), and 3 vitamin C treatment groups (125, 250, or 500 mg/kgBW + CPD 250mg/kgBB). Results: The results of blood biomarker, urine analysis, and histopathological analysis showed that CPD induced nephrotoxicity characterized by an increase in urea levels from 21.79 mg/l to 156.65 mg/l, creatinine from 0.375 to 0.717 mg/l, urine protein from 0 to 2.7, with histopathological damage scores from mild to severe (scores 1-3). In the treatment groups, the average damage score was 1-2 (mild score). However, of the three doses used, only the 500 mg/kg dose had significantly improved biomarkers compared to the placebo group, including the urea, creatinine, and urine protein levels, as well as histopathological scores (p<0.05). Conclusions: Vitamin C at a dose of 250 mg/kgBW was able to prevent the increase of urea, creatinine, and urine protein levels, however, a higher dose (500 mg/kg) was required to provide optimal protection against renal structural damage caused by cyclophosphamide.